HUBUNGAN PELAKSANAAN DENGAN KEPUASAN PASIEN TENTANG KOMUNIKASI TERAPEUTIK DI IGD RS AISYIYAH KUDUS - Tri Suwarto; Y Yulisetyaningrum; Nur Hidayat (Prosiding University Research Colloquium, 2021)
Background: Therapeutic communication is an alternative in providing accurate information and establishing trusting relationship to the patients so that patients will feel satisfaction for the services they received. In Emergency Installation of RSU Aisyiyah Kudus. nurses made communication based on their daily working habits/routines and had not completely paid attention to technical standard communication correctly and properly. Objective: To identify the correlation between management and patients’ satisfaction on therapeutic communication. Method: This study was a descriptive correlational research by means of cross-sectional framework, and employed a total sampling method to obtain description of therapeutic communication management by nurses with a total number of 22 respondents based on inclusion criteria. Data was taken through observation, and to measure the rate of patients’ satisfaction it was done through quota sampling with a number of 112 respondents based on inclusion criteria. Result: From the observation result, therapeutic communication management completed by 22 nurses to 112 patients showed that nurses completed highly good therapeutic communication to 4 (3.6%) patients, completed that of good level to 49 (43.8%) patients, completed that of moderate level to 40 (35.7%) patients, and completed that poorly to 19 (17%) patients. Based on the collected questionnaires, it was obtained a description about patients’ satisfaction during being hospitalized in emergency installation, in which 9 patients (8%) were highly satisfied, 84 patients (75%) were satisfied, 19 patients (17%) were less satisfied, none of the patients felt unsatisfied. The bivariate Spearman Rank resulted in a significant correlation between management and patients’ satisfaction on therapeutic communication. Conclusion: Most of nurses in emergency installation had completed therapeutic communication fairly well and patients’ satisfaction on therapeutic communication was well satisfied, there was a significant correlation between management and patients’ satisfaction on therapeutic communication.